Time gated fluorescence spectroscopy in Barrett's oesophagus. Issue 1 (1st January 2003) - Ortner, M-A E J; Ebert, B; Hein, E; Zumbusch, K; Nolte, D; Sukowski, U; Weber-Eibel, J; Fleige, B; Dietel, M; Stolte, M; Oberhuber, G; Porschen, R; et al.
Abstract : Background and aims: Specialised intestinal metaplasia and its dysplastic transformation, which precedes cancer in Barrett's oesophagus cannot be differentiated in standard gastroscopy. The aim of this study was to investigate whether laser induced protoporphyrin IX fluorescence permits the detection of specialised intestinal metaplasia and dysplasia during endoscopy and to take biopsy specimens in a guided rather than random manner. Methods: In 53 patients with Barrett's oesophagus 5-aminolaevulinic acid was sprayed on the mucosa. Approximately 60 to 120 minutes later, biopsy specimens were taken based on point-like measurements of delayed fluorescence intensity ratios of protoporphyrin IX in vivo. Two independent pathologists examined the 596 biopsy specimens taken, 168 of which were selected to be investigated by a third pathologist. Among these specimens only those (n=141) with a consensus diagnosis by at least two pathologists and p53 expression as additional marker were included in the analysis. Results: The median of normalised fluorescence intensity (ratio of delayed PpIX fluorescence intensity to immediate autofluorescence intensity) in non-dysplastic specialised intestinal metaplasia (0.51, 68% CI 0.09 to 1.92) and low grade dysplasia (1.89, 68% CI 0.55 to 3.92) differed significantly (p<0.005). Dysplasia was detected at a rate 2.8-fold higher compared with screening endoscopy despite taking fewer specimens. In addition, three early cancers were detected for the first time. Moreover, this method permitted differentiation of specialised intestinal metaplasia from junctional or gastric-fundic type epithelium (p<0.013). Conclusions: For the first time it was possible to differentiate low grade dysplasia from non-dysplastic Barrett's mucosa during endoscopy based on delayed laser induced fluorescence endoscopy of PpIX. Furthermore, the method helps to detect specialised intestinal metaplasia in short Barrett's oesophagus.